Ground dried okra (Abelmoschus esculentus L.) as fat replacer in macaroons. - Odtujan, Ivy Ysabelle Grumo (2015.)
The study was conducted in a Ramdomnized Complete Block Design with four treatments. The treatment was the amount of ground dried okra substituted to butter in each formulation. Fresh okra pods were dried in a cabinet dryer at 60-65°C for 6 hours. Butter in macaroon was substituted with ground dried okra in varying ratios: F1 (75:25), F2 (50:50), F3 (25:75) and F4 (0:100). F2 was the most preferred formulation of macaroon (MPFM) and gained equal rating of like very much with F1. F4 was the least preferred and received a rating of like slightly. MPFM was then compared to the control through proximate analysis and sensory evaluation. The proximate composition of MPFM : moisture content, 15.55%; crude protein, 5.30%; crude fat, 19.36%, ash, 2.08%; crude fiber, 3.58% and carbohydrates, 54.14%. Crude protein, ash content, crude fiber and carbohydrates content were higher than the control. Proximate composition of control : moisture content, 16.90%; crude protein, 4.73%; crude fat, 24.24%; ash, 1.82%; crude fiber, 2.66% and carbohydrates, 49.66%. The sensory characteristics of MPFM and control were compared through descriptive test. Scores for the color, texture, appearance and flavor of control showed that it had better quality than MPF. Even though the control had higher scores, MPF was more preferred over the control. MPF was also acceptable to the target consumers : working group, college students and grade school pupils. The working group of consumers rated the sample like very much. College students rated the sample like moderately and like very much for grade school pupils.
Thesis (Undergraduate. Bachelor of Science in Food Technology)School of Technology, University of the Philippines in the Visayas. 2015.
Keywords: Okra; Abelmoschus esculentus L; Macaroons